THE ROLE OF THE GOVERNMENT IN PROTECTING THE HUMAN RIGHTS OF CIVILIAN PAPUA IN RELATION TO THE EXISTENCE OF KKB AS TERRORISM IN THE PERSPECTIVE OF JUSTICE - Rosalina Indah Sari (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The conflict in Papua has significant implications for the national security system. The presence of KKB groups that continue to carry out brutal acts of terrorism, even targeting the Papua community, has compelled the government to make maximum efforts in apprehension. Attacking the KKB group becomes necessary because based on a long history of government from the time of President BJ Habibie (1998-1999) to the Jokowi administration, no peaceful agreement or resolution has been reached with the KKB. Instead, their criminal actions have become more brutal. These actions are taken in accordance with the fourth paragraph of the Preamble of the 1945 Constitution, which states the aspirations and goals of establishing a government, namely to protect the entire Indonesian nation and all of its descendants. Although the Jokowi government has made significant efforts to provide considerable attention to the people of Papua through infrastructure development to achieve the welfare of the Papuan people, the conflict with the KKB is not merely an economic and welfare issue. The presence of the KKB poses a threat to the national security system, thus necessitating law enforcement efforts within it and the protection of the rights of the Papuan people. The classification of the KKB as terrorists is based on their actions. Although some parties, such as the National Commission on Human Rights (Komnas HAM), argue that such labeling may cause unrest in the Papua community, the government's statements regarding this labeling have been criticized. However, the government labels them with the aim of facilitating efforts to eradicate the KKB group in order to protect the people of Papua and the national community as a whole. The government, through law enforcement agencies, is striving to resolve the issues and conflicts in Papua in order to protect human rights, particularly the civilian victims who are considered innocent but have always been victims in the series of conflicts with the KKB.